2021
DOI: 10.1097/rlu.0000000000003706
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Cutaneous Angiosarcoma in the Scalp and Face Demonstrated on FDG PET/CT Imaging

Abstract: Diffuse cutaneous angiosarcomas are rare. Herein, we reported FDG PET/CT findings of cutaneous angiosarcoma in a 59-year-old man. FDG PET/CT imaging was performed for staging, showing diffuse intense FDG uptake with an SUVmax of 19 in the scalp and face. Chemotherapy was recommended for this patient because surgery and radiotherapy were not appropriate due to the widespread skin involvement. Our case suggests that cutaneous angiosarcoma can present with diffuse skin involvement, and FDG PET/CT plays an importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…[3][4][5] Angiosarcoma of the abdominal aorta, skin, spleen, breast, and heart also showed intense FDG activity. [6][7][8][9][10] However, this case indicates that hepatic angiosarcoma does not necessarily present with increased FDG activity than the normal liver, and it should be taken into consideration as one of the possibilities in multiple hepatic masses with mild FDG activity.…”
mentioning
confidence: 88%
“…[3][4][5] Angiosarcoma of the abdominal aorta, skin, spleen, breast, and heart also showed intense FDG activity. [6][7][8][9][10] However, this case indicates that hepatic angiosarcoma does not necessarily present with increased FDG activity than the normal liver, and it should be taken into consideration as one of the possibilities in multiple hepatic masses with mild FDG activity.…”
mentioning
confidence: 88%
“…An MRI scan of the right shoulder (images not shown) from an outside institution reported that the mass was T1 isointense, T2 hyperintense to muscle with diffusion restriction and significant enhancement on postcontrast images. The findings suggested a malignant cutaneous lesion and likely sarcoma, for which FDG PET/CT was performed for staging 1–6 . The maximum intensity projection (MIP) image ( A ) showed a solitary intense activity in the right shoulder (arrow).…”
mentioning
confidence: 99%
“…The findings suggested a malignant cutaneous and likely sarcoma, for which FDG PET/CT was performed for staging. [1][2][3][4][5][6] The maximum intensity projection (MIP) image (A) showed a solitary intense activity in the right shoulder (arrow). On the axial images of the shoulders (B: PET, C: CT, D: fusion), the activity (arrow) was in the posterior right shoulder with maximum standardized uptake value (SUVmax) of 18.3 in comparison to hepatic SUVmax of 2.8, which corresponded to a lobulated soft tissue mass about 5.2 Â 3.4 Â 3.7 cm (arrow) without adjacent muscle or bone involvement.…”
mentioning
confidence: 99%